Scale-up of dehydrogenation reaction system via heterogeneous metal catalysts for the utilization of by-product glycerol from biodiesel production process - Song, Doyeon; Min, Juwon; Baek, Seung Jun; Song, In Hyoup; Park, Myung June; Valekar, Anil H.; Chandgude, Macchindra G.; Kyu Hwang, Young; Ha, Kyoung Su (Journal of Industrial and Engineering Chemistry, 2024)
Due to the increased waste glycerol from biodiesel process, this study focuses on scale-up of a reaction system for glycerol dehydrogenation to lactic acid and its derivatives using the Pt/ZrO2 catalyst. A concentration–time profile was obtained, based on which reaction mechanism and a reaction rate model were determined. The Langmuir–Hinshelwood model was used to develop the reaction rate model, which accurately predicted conversion of glycerol and yield of lactate, within a 5% error bounds. Based on these predictions, the volume of a continuous stirred-tank reactor (CSTR) was successfully estimated under the same reaction conditions. The calculated volume was approximately 60% of the batch volume indicating that reactor can become significantly more compact if the continuous reactor type could be used. Additionally, a pilot-scale CSTR volume was calculated by reflecting the adjusted reaction rate parameters, which were estimated from the experimental study of the pelletized catalyst. Furthermore, a reaction system with three CSTRs in series could reduce the total reactor volume by 65% than that obtained using a single CSTR. The results could be used as basic data for the scale-up of the continuous reaction system, where glycerol dehydrogenation takes place over the Pt/ZrO2 catalyst.
Keywords: Continous reactor; Continuous reactor design; Continuous stirred tank reactor; Kinetic models; Organic waste resource; Organic wastes; Reactor designs; Scale-up; Waste resources; ]+ catalyst; Continuous reactor design; Dehydrogenation; Glycerol; Kinetic modeling; Organic waste resources; Scale-up